KOMPETENSI MANAJERIAL DAN SUPERVISI MEMODERASI PENGARUH KEPUASAN TERHADAP KINERJA GURU - Ridwan, Ridwan (Students Journal of Economic and Management, 2012)
This studyaimed toanalyze the effect ofJob SatisfactionforPrimary SchoolTeacher PerformanceUnit ofDistrictEducation OfficeManagerialCompetenceTersonowiththe Principal andTeacherSupervisionas amoderatingvariable. In this studypopulation ofallprimary schoolteachersin DistrictTersonoPNS, whereassamples takenby 97persons asrespondentswithpurposivesampling. Withall ofthe criteria ofcivil servants inUPTTersonoDistrictEducation Office. Measurementsusing aLikert scaleof 7 (seven) alternative answers.Testinstrumentsused arevalidity and reliability. While thetestmodel usedis thecoefficient of determinationand F test(goodnes of Fit). Testingthe hypothesisin this study usingregression analysis.The results showedthe coefficient ofdetermination (Adjusted R Square) of 0.371, meaning thatJob Satisfaction, ManagerialCompetenceandSupervisionPrincipalTeachersin Learningtogether hold37.1%of theinfluenceon theTeacher PerformanceUnitTersonoDistrictEducation Officeand the remaining62.9%influenced byother variables that arenot includedin the study. Based on theresults ofthe studycan be summarized asfollows: (i) Job Satisfactionpositive effect onteacherperformance, (ii) PrincipalManagerialCompetencedoes nothave a positiveand significant impact onteacherperformance, (iii) SupervisingTeacherin Learningdoes nothave a positive andsignificant impact onteacherperformance,(iv) PrincipalManagerialCompetencemoderatingtheinfluencemememperkuatTeacherJob Satisfactionto Performance, (v) Supervision ofTeachersin Educationnot moderatethe influence ofTeacherJob Satisfactionto Performance. Keywords: Job Satisfaction, PrincipalManagerialCompetence, and TeacherPerformance.